Google Trends Search for Sex Reveals Change in Relationship Preferences in Post-Quarantine Periods in Chile (Journal of Advanced Research in Social Sciences, 2022)
The study investigated seasonal variations in mating behavior by analyzing the search for sex during the COVID-19 quarantine in Google trends. Causal impact analyses were used to examine the trends of Google keyword searches during the period in which the quarantine and post-quarantine period lasted in Chile, for topics related to mate preferences. Results indicated a consistent difference during the post-quarantine peaks of Google trends related to short-term and long-term mating behaviors. Such results complement research about the change in mating strategies from an evolutionary approach which predicted decreased a long-term investment during periods of uncertainty caused by the pandemic. We discuss the implications of this method to advance the comprehension the effects of pandemic on mating preferences.